Pollen morphology in Saxifraga (Saxifragaceae) from NyǺlesund, Svalbard, Arctic, and its taxonomic significance - Yifeng, Yao; Subir, Bera; Ferguson, David Kay; Chengsen, Li (Polar Research Institute of China - PRIC, 2014)
Pollen morphology of eight species of Saxifraga, i.e. S. cespitosa, S. oppositifolia, S. cernua, S. nivalis, S. aizoides, S. rivularis, S. hieraciifolia, and S. hirculus, collected from Ny-Ǻlesund, Svalbard, Arctic was examined using light and scanning electron microscopy. Pollen grains of Saxifraga species are subprolate or prolate, 3-colpate, 15.4–44.4 μm in the polar axis, 11.4–34.6 μm in the equatorial axis, and show a P/E ratio 1.19–1.40. On the basis of exine ornamentation, four pollen types, viz., the S. oppositifolia type (striate without scabrae on the muri), S. cernua type (striate with scabrae on the muri), S. nivalis type (microreticulate and operculum absent), and S. cespitosa type (microechinate and operculum present), were recognized. Hierarchical cluster analysis of the pollen morphological characters indicated that pollen morphology supports the infrageneric classification of the genus Saxifraga.